A REGULATION OF HILAL DETERMINATION IN INDONESIA AND ITS IMPLICATIONS FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Yulia Rahmadani Hudaya; Tri Aulia Pratiwi; Hardianto; Syamsuddin (UIN Palopo, 2025)
This research is motivated by the persistent discrepancies in hilal (crescent moon) determination in Indonesia, specifically between the hisab and rukyat methods, which not only affect individual and collective religious practices but also carry significant implications for the harmony of Muslim family life. While previous studies have predominantly focused on astronomical and jurisprudential aspects, the specific implications for Islamic family law remain relatively underexplored, highlighting the significance of this study. This research aims to analyze the regulations of hilal determination in Indonesia and examine their impact on legal certainty and religious practices from the perspective of Islamic family law. Employing a qualitative method with a normative-juridical approach through library research, this study analyzes statutory regulations, Islamic legal literature, and relevant academic articles. The findings reveal that while the regulation of hilal determination reflects an integration of Islamic and national law through the state's role in the Isbat council, the methodological divergence continues to cause legal and social inconsistencies. These variations result in non-uniformity in religious timing, which ultimately affects legal certainty and the harmony of religious observance within Muslim families. Consequently, this study suggests that a harmonization of hilal determination regulations is essential to realize legal certainty, unity in worship, and the overall stability of Muslim family life.